Influence of gait manipulation on running economy in female distance runners - Tseh, W.; Caputo, J. L.; Morgan, D. W. (Journal of Sports Science & Medicine, 2008)
The aim of this investigation was to determine if gait manipulation influences running economy. Following 30 minutes of accommodation to level treadmill running at 3.35 m·s-1 and determination of VO2peak, nine female distance runners (age = 23.3 ± 4.2 years; body mass = 57.5 ± 5.2 kg; height = 1.64 ± 0.10 m; body fat = 11.4 ± 2.4 %; VO2peak = 54.9 ± 4.1 ml·kg-1·min-1) completed two treadmill running sessions. In each session, standing VO2 was measured and subjects ran for 6 minutes at 3.35 m·s-1 under 4 randomly-selected conditions: a) normal running (NL), b) hands behind back (BK), c) hands on head (HD), and d) running with exaggerated vertical oscillation (VOSC). During the last 2 minutes of each running bout, samples of expired air were analyzed to determine oxygen uptake (VO2). Data obtained by averaging gross VO2 values across sessions indicated that VOSC (51.0 ± 2.5 ml·kg-1·min-1) and HD (46.1 ± 2.0 ml·kg-1·min-1) resulted in significantly (p < 0.05) elevated VO2 values compared to BK (43.9 ± 2.4 ml·kg-1·min-1) and NL (43.4 2.6 ml·kg-1·min-1). VO2 measured during VOSC was also higher compared to HD. Viewed in concert, these results suggest that specific gait manipulations can produce marked decrements in running economy among trained female distance runners.